Improved classification of Orthosiphon stamineus by data fusion of electronic nose and tongue sensors - Ammar, Zakaria; Ali Yeon, Md. Shakaff, Prof. Dr.; Abdul Hamid, Adom, Assoc. Prof. Dr.; Mohd Noor, Ahmad; Maz Jamilah, Masnan; Abdul Hallis, Abd Aziz; Nazifah, Ahmad Fikri; Abu Hassan, Abdullah; Latifah Munirah, Kamarudin (MDPI Publishing, 2011)
Link to publisher's homepage at http://www.mdpi.com/